Technology in Jain Harivansh Purana: With Special Focus on Travelling by Air - Jain, Alka; Jain, Sanyam (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2015)
Jagdish Chandra Basu proved through his experiments that all the plants and trees are alive and have feelings just like a human being has. He proved that plants react, laugh and also feel sad. This was proved in late ninetees. But Jain Agamas have been thesource of this information for last 2500 years.Acharang Sutra speaks a lot about ‘Vanaspati Kayik Jeeva’ (souls living in the bodies of plants and trees) and their feelings.The details are so live that one gets emotional for these so called non-living things.Not only vanaspati (plants) but prithvi (earth), Apkaay (water), tejas (fire) Vayu (air) are also alive as per Jain Canons. Unfortunately, modern generations do not believethese facts until and unlessthey are proved by some scientific approach. Hence plants are considered to be alive after Jagdish Chandra Basu’s experiments, while other four types of Kayik Jeevas are considered to be non-living thing still now. No one believed the stories of ‘Pushpaka Vimana’ in the Epic Ramayana as ‘people flying in air’ was not a scene that men of that era could imagine, but today we can see a large number of aeroplanes taking a lot of humans from one place to the other by air. Though inclination of scientists towards Indian Hindu literature is appreciable who are exploring ancient scriptures of Hindus for old technologies and ancient theories with new searches and researches based on the information provided in ancient literature ,but Jain literature has not been explored well till now while they have case studies of modern sciences like dream interpretation, medical sciences, colour therapies etc.This study attempts to explore an ancient Jain book ‘Harivansh Purana’ for case studies of air travel. The authors have listed and interpreted case studies from the book which give us a glimpse of flying technologies used in that era, users of the technolgy Further scope of this study can be to prove all the technological evidences in modern theories and references. Modern interpretation of thesetheories may bring out the truth that ancient Indian stories are not just myths, they have strong technological roots and evidences in their ancient literature Further Scope of Study can be to analyse the case studies in Harivansh Purana for other sciences and technologies also. The authors have focused on flying technology in Harivansh Purana but the fact is that the book is dotted with case studies of many other sciences and technologies like dream interpretation, medical science, architectural sciences, numerology etc. too. A list of armours used in the battles can also be listed. A listof sciences and technologies available in that era has also been given in the book like Pragyapti and maya etc. Experts of various fields should come forward to explore Jaina treasure of sciences for the modern world.